Vaccine Elicitation of High Mannose-Dependent Neutralizing Antibodies against the V3-Glycan Broadly Neutralizing Epitope in Nonhuman Primates - Kevin O. Saunders; Nathan I. Nicely; Kevin Wiehe; Mattia Bonsignori; R. Ryan Meyerhoff; Robert Parks; William E. Walkowicz; Baptiste Aussedat; Nelson R. Wu; Fangping Cai; Yusuf Vohra; Peter K. Park; et al. (Cell Reports, 2017)
Summary: Induction of broadly neutralizing antibodies (bnAbs) that target HIV-1 envelope (Env) is a goal of HIV-1 vaccine development. A bnAb target is the Env third variable loop (V3)-glycan site. To determine whether immunization could induce antibodies to the V3-glycan bnAb binding site, we repetitively immunized macaques over a 4-year period with an Env expressing V3-high mannose glycans. Env immunizations elicited plasma antibodies that neutralized HIV-1 expressing only high-mannose glycans—a characteristic shared by early bnAb B cell lineage members. A rhesus recombinant monoclonal antibody from a vaccinated macaque bound to the V3-glycan site at the same amino acids as broadly neutralizing antibodies. A structure of the antibody bound to glycan revealed that the three variable heavy-chain complementarity-determining regions formed a cavity into which glycan could insert and neutralized multiple HIV-1 isolates with high-mannose glycans. Thus, HIV-1 Env vaccination induced mannose-dependent antibodies with characteristics of V3-glycan bnAb precursors. : Most bnAb epitopes on HIV-1 Envelope include host glycans, but previous Env vaccines have not induced glycan-dependent antibodies. Saunders et al. describe here the ontogeny, crystal structure with glycan, and virion Man9GlcNAc2-dependent neutralization for glycan-reactive antibodies induced by envelope vaccination. Keywords: HIV, V3 glycan, vaccination, glycan, long-term immunization